On the Emergence of Twin Primes - Ouannas Moussa (Mathematics and Computer Science: Contemporary Developments Vol. 9, 2024)
One of the most famous problems in mathematics is the Twin Prime Conjecture. This study gives an idea of how and when twin prime numbers emerge while remaining within the set of natural numbers.